Disturbed default mode network connectivity patterns in Alzheimer's disease associated with visual processing - Krajcovicova, Lenka; Mikl, Michal; Marecek, Radek; Rektorova, Irena (Journal of Alzheimer's disease, 2014)
Changes in connectivity of the posterior node of the default mode network (DMN) were studied when switching from baseline to a cognitive task using functional magnetic resonance imaging. In all, 15 patients with mild to moderate Alzheimer's disease (AD) and 18 age-, gender-, and education-matched healthy controls (HC) participated in the study. Psychophysiological interactions analysis was used to assess the specific alterations in the DMN connectivity (deactivation-based) due to psychological effects from the complex visual scene encoding task. In HC, we observed task-induced connectivity decreases between the posterior cingulate and middle temporal and occipital visual cortices. These findings imply successful involvement of the ventral visual pathway during the visual processing in our HC cohort. In AD, involvement of the areas engaged in the ventral visual pathway was observed only in a small volume of the right middle temporal gyrus. Additional connectivity changes (decreases) in AD were present between the posterior cingulate and superior temporal gyrus when switching from baseline to task condition. These changes are probably related to both disturbed visual processing and the DMN connectivity in AD and reflect deficits and compensatory mechanisms within the large scale brain networks in this patient population. Studying the DMN connectivity using psychophysiological interactions analysis may provide a sensitive tool for exploring early changes in AD and their dynamics during the disease progression.
Keywords: Alzheimer's disease; senioři; functional MRI; senioři nad 80 let; Neuropsychological Tests; Male; počítačové zpracování obrazu; zrakové dráhy; default mode network; Brain Mapping; mužské pohlaví; posterior cingulate; studie případů a kontrol; Alzheimer Disease; mozek; visual processing; magnetická rezonanční tomografie; Aged, 80 and over; Magnetic Resonance Imaging; kyslík; Brain; ženské pohlaví; Nerve Net; neuropsychologické testy; Visual Pathways; Humans; mapování mozku; nervová síť; Image Processing, Computer-Assisted; Alzheimerova nemoc; Oxygen; Female; Aged; lidé; Case-Control Studies